TANTANGAN PEMBELAJARAN DARING SELAMA PANDEMI COVID-1 - Mega T. Lumbantobing; Afrida Samosir; Dinda Renita Br Tarigan (EJoES (Educational Journal of Elementary School), 2020)
The world of education is being hit by a learning crisis due to the presence of the Covid 19 virus so that learning is transferred to the network. Various obstacles arise in online learning. This study aims to investigate the challenges that arise during online learning. This type of research is library research using data sources from books, articles and journals. Based on the results of the analysis, it was found that students did not have learning tools, the teacher's ability to operate technology was limited and the availability of internet networks was difficult.